Altered brain perfusion patterns in wakefulness and slow-wave sleep in sleepwalkers. Issue 5 (3rd March 2018) - Desjardins, Marie-Ève; Baril, Andrée-Ann; Soucy, Jean-Paul; Dang-Vu, Thien Thanh; Desautels, Alex; Petit, Dominique; Montplaisir, Jacques; Zadra, Antonio
Abstract: Study Objectives: The present study assessed brain perfusion patterns with single-photon emission computed tomography (SPECT) during sleepwalkers' post-sleep deprivation slow-wave sleep (SWS) and resting-state wakefulness. Methods: Following a 24 hr period of sleep deprivation, 10 sleepwalkers and 10 sex- and age-matched controls were scanned with a high-resolution SPECT scanner. Participants were injected with 99m Tc-ethylene cysteinate dimer after 2 min of stable SWS within their first sleep cycle as well as during resting-state wakefulness, both after a subsequent 24 hr period of sleep deprivation. Results: When compared with controls' brain perfusion patterns during both SWS and resting-state wakefulness, sleepwalkers showed reduced regional cerebral perfusion in several bilateral frontal regions, including the superior frontal, middle frontal, and medial frontal gyri. Moreover, reduced regional cerebral perfusion was also found in sleepwalkers' left postcentral gyrus, insula, and superior temporal gyrus during SWS compared with controls. During resting-state wakefulness compared with controls, reduced cerebral perfusion was also found in parietal and temporal regions of sleepwalkers' left hemisphere, whereas the right parahippocampal gyrus showed increased regional cerebral perfusion. Conclusions: Our results reveal patterns of reduced regional cerebral perfusion in sleepwalkers' frontal and parietal areas when compared with controls, regions previously associated with SWS generation and episode occurrence. Additionally, reduced perfusion in the dorsolateral prefrontal cortex and insula during recovery SWS is consistent with the clinical features of somnambulistic episodes, including impaired awareness and reduced pain perception. Altered regional cerebral perfusion patterns during sleepwalkers' resting-state wakefulness may be related to daytime functional anomalies in this population.